2022
DOI: 10.3390/molecules27175466
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity of Herzegovinian Wildflowers Evaluated by UV–VIS and Cyclic Voltammetry Analysis

Abstract: Considering the vast cultural and traditional heritage of the use of aromatic herbs and wildflowers for the treatment of light medical conditions in the Balkans, a comparison of the antioxidant capacity of wildflowers extracts from Herzegovina was studied using both cyclic voltammetry and spectrophotometry. The cyclic voltammograms taken in the potential range between 0 V and 800 mV and scan rate of 100 mV s−1 were used for the quantification of the electrochemical properties of polyphenols present in four aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The vibration modes of other functional groups that could furthermore confirm the identity of phenolic acid adsorbed on the ALA surface could be overlapping with the vibration modes of the main corrosion products of both samples: γ-Al 2 O 3 and α-Al 2 O 3 . Our recent study showed that the oxidation of phenolic components responsible for the antioxidant activity of the aqueous extract of A. annua was reversible and that one of the main components of the examined plant extract was caffeic acid [ 42 ]. Earlier studies reported that the main organic components of A. annua aqueous extract were caffeic and feruloyl-quinic acid derivative [ 48 , 49 ], while this study confirmed that small molecules, such as chlorogenic and caffeic acid, readily diffused to the aqueous phase during 3 h maceration at room temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vibration modes of other functional groups that could furthermore confirm the identity of phenolic acid adsorbed on the ALA surface could be overlapping with the vibration modes of the main corrosion products of both samples: γ-Al 2 O 3 and α-Al 2 O 3 . Our recent study showed that the oxidation of phenolic components responsible for the antioxidant activity of the aqueous extract of A. annua was reversible and that one of the main components of the examined plant extract was caffeic acid [ 42 ]. Earlier studies reported that the main organic components of A. annua aqueous extract were caffeic and feruloyl-quinic acid derivative [ 48 , 49 ], while this study confirmed that small molecules, such as chlorogenic and caffeic acid, readily diffused to the aqueous phase during 3 h maceration at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The significant antioxidant activity of plant extracts is not restricted to a particular family and is mostly attributed to the synergetic effect of active constituents found in the extracts [ 20 ]. Our recent study suggests that Artemisia annua L. harvested in its naturally occurring habitat in Herzegovina exhibits high antioxidant activity and has a high content of phenolics, flavonoids, and tannins [ 42 ]. Artemisia annua L. is a wildflower known in traditional medicine for centuries [ 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…These tubes were then incubated at 4 • C for 4 h and centrifuged at 3000 rpm for 10 min at 4 • C. After centrifugation, the supernatant was collected, and the non-tannin phenolics were measured using the same method to determine the total phenolics. The tannin content was determined by subtracting the non-tannin phenolics from the total phenolics [29]. The results were reported in milligrams of gallic acid equivalents per gram of dry weight of the extract, along with the SD for three replicate analyses.…”
Section: Determination Of Total Tanninmentioning
confidence: 99%